IMPACT OF ADVANCED HEMODYNAMIC MONITORING ON MYOCARDIAL REVASCULARIZATION SURGERY IN HIGH-RISK PATIENTS - Djosci Coêlho de Sá, Henrique; Costa de Mello Farah, Vinicius; Fernandes Alevato, Lucca; Zanetti Pinheiro, Thiago; Víctor Elias Sobrinho, Paulo; Sérgio Martins Neto, José; Andre Ramalho Rangel Lima, Paulo; Bandeira de Mello Sanches de Almeida, Eduardo; Hugo Mendes da Cunha, Vitor; Vitor Gullo de Oliveira Ribeiro, Antônio; Tibério Campos Calegário, Luiza; de Oliveira Figueiredo, Bruno (Health and Society, 2024)
Coronary artery bypass grafting is a critical procedure for patients with advanced coronary disease, especially those classified as high risk due to comorbidities such as heart failure, hypertension and diabetes. Advanced hemodynamic monitoring has proved essential in this context, allowing continuous and accurate surveillance of cardiac and vascular parameters, which can reduce intra- and post-operative complications. This abstract aims to assess the impact of advanced hemodynamic monitoring during coronary artery bypass graft surgery in high-risk patients. The aim is to explore the advantages of this type of monitoring, the technologies used and the benefits in terms of clinical outcomes and reduction of complications. This is a literature review with a qualitative approach, carried out in the PubMed, SciELO, LILACS, BVS and Google Scholar databases. In order to optimize the search, descriptors such as Hemodynamic Monitoring, Cardiac Surgery, High Risk Patients and Fluid Management were used. For time delimitation, the research considered publications between the years 2019 and 2022, a period that reflects the latest advances in hemodynamic monitoring technologies in high-risk cardiac surgeries. Advanced hemodynamic monitoring includes the use of devices such as the pulmonary artery catheter and non-invasive bioimpedance systems, which provide real-time data on cardiac output, blood pressure, oxygen saturation and systemic vascular resistance. In high-risk patients, these devices allow for precise adjustments in the administration of fluids and vasoactive drugs, promoting better hemodynamic stability. Studies indicate that this approach reduces the incidence of serious complications, such as cardiogenic shock and arrhythmias, optimizing post-operative recovery. Therefore, advanced hemodynamic monitoring is a crucial tool in CABG surgeries, especially for high-risk patients. Its implementation improves intraoperative management, reducing the risk of complications and promoting better clinical outcomes. Therefore, its use should be considered an integral part of strategies for complex cardiac surgeries.